1987
DOI: 10.1002/jez.1402430210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium antagonists, calmodulin antagonists, and methylated xanthines on polar lobe formation and cytokinesis in fertilized eggs of Ilyanassa obsoleta

Abstract: We have studied the ability of fertilized eggs of Ilyanassa obsoleta to undergo polar lobe formation and cytokinesis in the presence of Ca2+ antagonists (Ca2+ channel blockers, Ca2+ uptake inhibitors). Earlier work had suggested little need for exogenous Ca2+ during these cellular shape changes. Again it appears that exogenous Ca2+ probably is not required, based on cell ability to undergo the shape changes with no, or only minor, delay in the presence of 50 mM La3+ at pH 6.5, 10 mM concentrations of Ni2+ or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This inhibitor does not affect polar lobe formation and cytokinesis, as was found previously for Ilyanassa (Conrad et al 1987). In addition, D600…”
Section: Effects Of D600 and Tmb-8supporting
confidence: 66%
See 1 more Smart Citation
“…This inhibitor does not affect polar lobe formation and cytokinesis, as was found previously for Ilyanassa (Conrad et al 1987). In addition, D600…”
Section: Effects Of D600 and Tmb-8supporting
confidence: 66%
“…The possible role of calcium released from intracellular stores was investigated using TMB-8, which is an antagonist of intracellular calcium mobilization and is known to affect normal polar lobe formation in Ilyanassa (Conrad et al 1987). We found that continuous incubation with 200 ~tM TMB-8 concomitantly with Con A treatment prevents the occurrence of typical Con A-induced effects.…”
Section: Effects Of D600 and Tmb-8mentioning
confidence: 96%
“…How are these suspected [Ca2+]i gradients generated and what are their likely targets? Our earlier work (10) suggested that, in addition to [Ca2+]i gradients, PIP2 turnover and Ins (1,4,5)P3-induced Ca 2+ release were required for normal cleavage. Thus, components of the inositol cascade may well be involved in this [Ca2+]~ gradient generation.…”
Section: Discussionmentioning
confidence: 99%
“…Imposed increases in [Ca2+]~ have been shown to induce nuclear envelope breakdown in both sea urchin eggs and mammalian 3T3 fibroblasts, while suppressing [Ca2+]t changes with the calcium buffer, BAPTA, inhibited nuclear envelope breakdown in sea urchin eggs and Swiss 3T3 cells (15,28). Elevation of [Ca2+]~ in squid eggs by treatment with the calcium ionophore, A23187 (1), and in llyanassa eggs by treatment with caffeine (5), has been shown to speed the onset of cleavage. Cell division was retarded in sea ur-chin (33), medaka (8), and Xenopus (10,19) embryos in which [Ca2+]i changes were suppressed with the BAPTA family of buffers and earlier work with much higher concentrations of EGTA also resulted in some cleavage inhibition (2,31).…”
mentioning
confidence: 99%
“…During phase I, a period lasting 50 ? 5 min (timing of phases I-IV: Conrad et al [1987]), the PLC constricts at a constant slow rate to deform the egg into a pear shape ( Fig. 1: Cont 30 min), while the mitotic apparatus forms, expands, and then disassembles in the animal hemisphere.…”
Section: Ions Alter Contractile Ring Dynamics At First Cleavagementioning
confidence: 99%